The Pengembangan buku panduan permainan tradisional dalam pembelajaran matematika tema 2 untuk siswa kelas II SD - Widyawati, Agnes Gonzha; Aprinastuti, Christiyanti; Mayasari, Elisabeth Desiana (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
This research is motivated by the lack of reference books for teachers to convey mathematics learning through traditional games so that students can learn with fun. This study aims to (1) describe the procedures for developing a traditional games guide book in mathematics learning 2nd themes for second grade of elementary school; and (2) knowing the quality of traditional games guide book in mathematics learning 2nd themes for second grade of elementary school. This research is a type of research and development (R&D). The subjects of this research were a second-grade teacher at Kanisius Jomegatan Elementary School and Nyamplung Elementary School. The object of this research is a traditional games-based guidebook in mathematics learning on 2nd themes for the second grade of elementary school students. The data in this research were collected using interviews, observation, and questionnaire techniques. The results showed that: (1) the procedure of research and development of a traditional game-based guide book in mathematics learning on 2nd themes for second grade of elementary school students using the ADDIE model development steps, namely Analyze, Design, Development, Implementation, and Evaluate; (2) the quality of traditional game manuals in mathematics learning Theme 2 grade II elementary school is “Very Good” with a score of 3.05 from a scale 4.00 and fulfilling ten criteria of guidebooks according to Greene and Petty (Utomo, 2008: 45).